Porous carbon derived from metal–organic framework@graphene quantum dots as electrode materials for supercapacitors and lithium-ion batteries. Issue 17 (26th March 2019) - Yu, Hui; Zhu, Wenjian; Zhou, Hu; Liu, Jianfeng; Yang, Zhen; Hu, Xiaocai; Yuan, Aihua
Abstract : The C@GQD composite was prepared by the combination of metal–organic framework (ZIF-8)-derived porous carbon and graphene quantum dots (GQDs) by a simple method. Abstract : The C@GQD composite was prepared by the combination of metal–organic framework (ZIF-8)-derived porous carbon and graphene quantum dots (GQDs) by a simple method. The resulting composite has a high specific surface area of 668 m 2 g −1 and involves numerous micro- and mesopores. As a supercapacitor electrode, the material showed an excellent double-layer capacitance and a high capacity retention of 130 F g −1 at 2 A g −1 . The excellent long-term stability was observed even after ∼10 000 charge–discharge cycles. Moreover, the composite as an anode material for a lithium-ion battery exhibited a good reversible capacity and outstanding cycle stability (493 mA h g −1 at 100 mA g −1 after 200 cycles). The synergistic effect of a MOF-derived porous carbon and GQDs was responsible for the improvement of electrochemical properties.